Sukuk Trend Analysis: Bibliometric and Systematic Literature Review from 2011 - 2021 - Ryan Rahmah Maulayati; Sri Iswati (Universitas Airlangga, 2023)
ABSTRACT The stability of Islamic finance has made many researchers interested in discussing Islamic finance. Sukuk is included in one of the widely published areas of Islamic finance, making it a topic of discussion in several scholarly forums. This study used the Scopus database, where there were 2,128 articles related to sukuk in the Scopus web in 2011-2021, but only 108 articles were included in the criteria and used as a research sample using bibliometric methods and SLR to obtain results related to publication activities, popular topics, research trends, and recommendations for research directions related to sukuk. In the bibliometric analysis method with the help of biblioshiny applications and SLR analysis by reviewing each article and grouping research topics. The results showed that sukuk related publication articles were spread in several countries that were not restricted. Malaysia is the country with the most publications related to sukuk, and most often conducts research collaborations in both Multiple Country Collaboration (MPC) and Single Country Collaboration (SCP). The results of SLR analysis have four themes that are most discussed in research related to sukuk, so researchers provide recommendations for further research directions that can be used by researchers in the future, such as adding research using qualitative methods or discussing the impact of sukuk performance in real terms not only from secondary data. Keywords: Bibliometric, Islamic Bond, Sukuk, Systematic Literature Review (SLR). ABSTRAK Stabilnya Keuangan Islami menjadikan banyak peneliti yang tertarik membahas Keuangan Islami. Sukuk termasuk dalam salah satu sektor Keuangan Islami yang banyak diterbitkan sehingga menjadikan sukuk sebagai topik bahasan diskusi dalam beberapa forum ilmiah. Penelitian ini menggunakan database scopus dimana terdapat 2.128 artikel terkait sukuk pada tahun 2011-2021 dalam web scopus, akan tetapi hanya 108 artikel yang masuk dalam kriteria dan dijadikan sampel penelitian dengan menggunakan metode bibliometrik dan SLR untuk mendapatkan hasil terkait aktivitas publikasi, tema popular, tren penelitian dan rekomendasi arah penelitian terkait sukuk. Pada metode bibliometrik analisis menggunakan bantuan aplikasi biblioshiny dan analisis SLR dengan melakukan review setiap artikel dan mengelompokkan tema penelitian. Hasil penelitian menunjukkan artikel publikasi terkait sukuk tersebar di beberapa negara yang tidak dibatasi. Malaysia merupakan negara dengan publikasi terbanyak terkait sukuk dan paling sering melakukan kolaborasi penelitian baik secara Multiple Country Collaboration (MPC) dan Single Country Collaboration (SCP). Hasil analisis SLR terdapat empat tema yang paling banyak dibahas dalam penelitian terkait sukuk, sehingga peneliti memberikan rekomendasi arah penelitian selanjutnya yang dapat digunakan oleh peneliti selanjutnya dengan menambah penelitian menggunakan metode kualitatif atau membahas dampak kinerja sukuk secara real bukan hanya dari data sekunder. Kata Kunci: Bibliometric, Islamic Bond, Sukuk, Systematic Literature Review (SLR).